1999
DOI: 10.1159/000007678
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory Effect of Nitric Oxide on Bicarbonate Secretion in Bullfrog Duodenums in vitro

Abstract: The effect of nitric oxide (NO) on HCO3 secretion was examined in vitro using an isolated preparation of bullfrog duodenum. The tissue was bathed in unbuffered Ringer’s solution gassed with 100% O2 on the mucosal side and HCO3 Ringer’s solution gassed with 95% O2–5% CO2 on the serosal side. The HCO3 secretion was measured by the pH-stat method using 2 mmol/l HCl as the titrant to keep the mucosal pH at 7.4. (±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 29 publications
(38 reference statements)
0
17
0
Order By: Relevance
“…We previously reported that the HCO 3 -response induced by cholinergic agents was not affected by indomethacin [18] . Furukawa et al [25] reported that NO stimulates the HCO 3 -secretion, mediated by endogenous PGs in isolated bullfrog duodenums. Thus, it is reasonable that the HCO 3 -response induced by nizatidine is not affected by the NO synthase inhibitor L-NAME.…”
Section: Figurementioning
confidence: 99%
“…We previously reported that the HCO 3 -response induced by cholinergic agents was not affected by indomethacin [18] . Furukawa et al [25] reported that NO stimulates the HCO 3 -secretion, mediated by endogenous PGs in isolated bullfrog duodenums. Thus, it is reasonable that the HCO 3 -response induced by nizatidine is not affected by the NO synthase inhibitor L-NAME.…”
Section: Figurementioning
confidence: 99%
“…Uno et al (35) reported that the NO donor S-nitroso-N-acetyl penicillamine stimulates PGE 2 production in rat gastric epithelial cells. Furukawa et al (8) reported that both NOR-3 and dibubutyryl guanosine-3Ј,5Ј-cyclic monophosphate increased PGE 2 production in isolated bullfrog duodenums, suggesting a NO/cGMP-dependent increase in PG production. In the present study, the increased PGE 2 generation after the mucosal acidification was blocked not only by indomethacin but also by L-NAME.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is also possible that mucosal acidification increases NO release through the stimulation of capsaicin-sensitive sensory neurons. On the other hand, several studies have reported that NO or NO donors stimulate PG production in various organs and cells (8,35,36). Uno et al (35) reported that the NO donor S-nitroso-N-acetyl penicillamine stimulates PGE 2 production in rat gastric epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The stimulatory effect of PGE 2 on HCO 3 Ϫ secretion in the stomach is known to be mediated by the activation of EP1 receptors and coupled intracellularly with Ca 2ϩ (Takeuchi et al, 1997b. In contrast, NO stimulates the secretion of HCO 3 Ϫ in the duodenum via the activation of soluble guanylate cyclase and an increase in the intracellular level of cGMP (Moncada et al, 1991;Furukawa et al, 1999;Sugamoto et al, 2001). We further showed that NOR-3, an NO donor, increased the secretion of HCO 3 Ϫ in the rat stomach, via endogenous PGE 2 in a cGMP-dependent manner .…”
Section: The Secretion Of Hcomentioning
confidence: 99%
“…It remains, however, unexplored which PDE isozyme(s) is involved in the regulation of gastric HCO 3 Ϫ secretion. The regulatory mechanism of HCO 3 Ϫ secretion differs in many points between the stomach and the duodenum; in the latter, the secretion is mediated intracellularly with both cAMP, cGMP, and Ca 2ϩ , whereas that in the stomach is intracellularly mediated by Ca 2ϩ and cGMP but not cAMP (Flemström, 1977(Flemström, , 1987Guba et al, 1996;Seidler et al, 1997;Takeuchi et al, 1997a;Furukawa et al, 1999;Rao et al, 2004;Sellers et al, 2005). Thus, there is a possibility that the PDE isozymes involved in the HCO 3 Ϫ response are different in these tissues.…”
Section: The Secretion Of Hcomentioning
confidence: 99%